Assessing for teaching and learning in the initial training of early childhood mathematics teachers: Towards Dynamic Assessment (Edma 0-6: Educación Matemática en la Infancia, 2021)
Dynamic Assessment (DA) is presented as a tool to promote the Professional Teacher Identity (PTI) of pre-service mathematics teachers of Early Childhood Education. The first part presents the theoretical foundations of DA, a socio-cultural approach based on an integrated view of teaching and assessment as part of the same process. From this perspective, in the second part, after conceptualizing IPD and the professional competences of pre-service early childhood teachers, an example of a Guide for using DE in the subject "Learning Mathematics" of the Early Childhood Education Teacher Training Degree at the University of Girona (Spain) is described. This guide includes three phases: 1) Momentary self-diagnosis; 2) Self-advancement and self-monitoring; and 3) Self-assessment of progress. It is concluded that this tool can be useful to train competent Early Childhood Mathematics teachers who are committed to their profession and proud to practice it.
Keywords: Dynamic Assessment; Mathematics Teacher Education; Professional development; Professional teacher identity; Early Childhood Education